Британская геостратегия в зоне Индийского океана накануне Второй мировой войны (Բրիտանական աշխարհառազմավարությունը Հնդկական օվկիանոսի շրջանում Երկրորդ համաշխարհային պատերազմի նախօրեին) - Մոստյաեվ, Յուրի (YSU Journal of International Affairs, 2014)
This article has a deal with the role of India in the system of defence of the British Empire on the eve of the Second World War. The Indian Ocean was Mediterranean Sea of the British Empire and played an important role in the defence capability of Britain. India was the heart of the English military strategyat the area of the Indian Ocean. The military doctrine of Great Britain has formed basically under geographical situation and centuries-old process of development of this colonial Power. The main tasks of the empire strategy were safeguarding of security sea communications, inadmissibility of their passing to the enemy; the defence Great Britain, the main arsenal, from the air attacks; the defence of land border of the Empire. All the countries, the members of the Empire, had to take part in these tasks. All this determined the military strategy of Britain to India. The defence of sea borders of India was realized by the Navy of common empire. During the war the strategic and geopolitics importance of India for the British Empire strongly increased.
Keywords: India, Great Britain, the Second World War, Indian Ocean, military doctrine